A Critical Study of English Language Teaching Methods in the Single National Curriculum (2020) for Primary Level in Pakistan - Muhammad Mujtaba Mitra Zuana; Afifa Hanif (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2025)
This research critically investigates English Language Teaching methods and practices employed within the framework of the Single National Curriculum (SNC) 2020, focusing on the primary grade level. This study aims to assess the efficacy of these methods in enhancing language acquisition among students in grades I-V and in achieving the broader goals of educational equity and standardization across the country. This research also evaluates the alignment of the Single National Curriculum with internationally recognized English Language Teaching frameworks to examine whether it equips students to meet global language competency standards. The findings of the study reveal that although the Single National Curriculum marks a significant advancement in standardizing English language education in Pakistan, there are critical gaps that need to be addressed. These include inconsistencies in teaching practices, especially in public schools, insufficient focus on essential language skills such as listening, and inadequate attention to teacher development opportunities. This research also delves into these practical challenges faced by teachers in implementing the curriculum in classrooms namely, resource constraints, lack of professional development, limited time, and the need for curriculum adaptation to local and global contexts. The study concludes that for the Single National Curriculum to fully realize its potential, there must be ongoing curriculum refinement, enhanced teacher training, and the development of more contextually relevant educational resources. These steps are essential for aligning the Single National Curriculum more closely with international English Language Teaching standards and for ensuring that it effectively meets the diverse needs of Pakistan’s primary school students, thereby fostering a more globally competitive and equitable education system.